Evaluating the quality, feasibility and patient satisfaction of medication history taking by telephone for patients with scheduled admissions: a pilot study - Terstegen, Theresa; Bittmann, Janina; Kauk, Luise; Kirchner, Marietta; Krug, Sebastian; Gauss, Annika; Chiriac, Ute; Morath, Benedict; Haefeli, Walter E.; Seidling, Hanna (International journal of clinical pharmacy, 2025)
Medication history taking at hospital admission is still prone to errors. Despite numerous quality improvement initiatives, new strategies to improve medication history taking are still sought and evaluated. Unfortunately, the gold standard research methodology for evaluation is resource-intensive, as it requires each patient to complete two medication history interviews. Therefore, a new study design and quality parameter were developed.
Gesehen am 15.01.2026